2013
DOI: 10.1007/s00792-013-0518-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects on microbial composition and microbiologically induced corrosion and mineral precipitation affecting operation of a geothermal plant in a deep saline aquifer

Abstract: The microbial diversity of a deep saline aquifer used for geothermal heat storage in the North German Basin was investigated. Genetic fingerprinting analyses revealed distinct microbial communities in fluids produced from the cold and warm side of the aquifer. Direct cell counting and quantification of 16S rRNA genes and dissimilatory sulfite reductase (dsrA) genes by real-time PCR proved different population sizes in fluids, showing higher abundance of bacteria and sulfate reducing bacteria (SRB) in cold flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 107 publications
(106 reference statements)
3
40
0
9
Order By: Relevance
“…Microbial habitats extend down to great depths beneath the earth's surface. However, cell counts and detailed characterizations of the microbial community structure in the continental deep biosphere are rare and mostly related to investigations in oil reservoirs (Youssef et al, 2009), geothermal aquifers (Alawi et al, 2011;Lerm et al, 2013) or gold mines (Deflaun et al, 2007;Takai et al, 2001;Trimarco et al, 2006). A few continental drilling campaigns have focused on the deep biosphere (Fredrickson et al, 1997;Onstott et al, 1998;Zhang et al, 2005), though the state of knowledge reached is still in the early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial habitats extend down to great depths beneath the earth's surface. However, cell counts and detailed characterizations of the microbial community structure in the continental deep biosphere are rare and mostly related to investigations in oil reservoirs (Youssef et al, 2009), geothermal aquifers (Alawi et al, 2011;Lerm et al, 2013) or gold mines (Deflaun et al, 2007;Takai et al, 2001;Trimarco et al, 2006). A few continental drilling campaigns have focused on the deep biosphere (Fredrickson et al, 1997;Onstott et al, 1998;Zhang et al, 2005), though the state of knowledge reached is still in the early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that saline aquifers are inhabited by elevated numbers of different groups of microorganisms (Goldscheider et al 2006;Basso et al 2009;Morozova et al 2010;Lerm et al 2013). The most important metabolic pathways in the deep biosphere are sulfate reduction, fermentation and in some cases, methanogenesis (Takai et al 2001;Kotelnikova 2002;Baker et al 2003;Basso et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, geothermal systems can only be qualified as renewable if there is a global annual thermal equilibrium. These potential environmental effects must be (and will increasingly be) studied because they can have strong economic repercussions such as lowering the global life of the system with side effects such as aquifer freezing and scaling on heat exchangers and wells [6,26,27]. From an economical point of view, a better knowledge of the thermal affected zone (TAZ) [28,29] can prevent shallow geothermal systems competing with each other (thermal feedback or thermal recycling) [30,31] or better, to take benefit of multiple ATES systems with mutual energy storage zones to enhance the global systems efficiency [22].…”
Section: Introductionmentioning
confidence: 99%